2016
DOI: 10.1242/bio.021071
|View full text |Cite
|
Sign up to set email alerts
|

Effects ofHd2in the presence of the photoperiod-insensitive functional allele ofHd1in rice

Abstract: The role of photoperiod sensitivity (PS) of flowering genes have become well recognized in rice, whereas little attention has been drawn to the non-PS component of these genes, especially to their influence on gene-by-gene interactions. Rice populations in which the photoperiod-sensitive allele at Hd1 has become insensitive to photoperiod but continued to affect heading date (HD) were used in this study to fine-map a quantitative trait locus (QTL) for HD and analyze its genetic relationship to Hd1. The QTL was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 39 publications
2
11
0
Order By: Relevance
“…Frontiers in Genetics | www.frontiersin.org January 2020 | Volume 11 | Article 13 ZS97 ( Supplementary Table S2). In previous studies using the same rice cross, the ZS97 alleles in the two regions were found to decrease HD (Zhang et al, 2011;Zhang et al, 2016). These results suggest that the pleiotropic effects of major heading-date genes on AAC with opposite directions could be a common occurrence.…”
Section: Xie Et Al Rft1 Affecting Amino Acid Contentmentioning
confidence: 59%
“…Frontiers in Genetics | www.frontiersin.org January 2020 | Volume 11 | Article 13 ZS97 ( Supplementary Table S2). In previous studies using the same rice cross, the ZS97 alleles in the two regions were found to decrease HD (Zhang et al, 2011;Zhang et al, 2016). These results suggest that the pleiotropic effects of major heading-date genes on AAC with opposite directions could be a common occurrence.…”
Section: Xie Et Al Rft1 Affecting Amino Acid Contentmentioning
confidence: 59%
“…Hd1 also plays a role in grain yield (Zhang et al 2016). To determine the viability and productivity of OX‐Hd1miP plants in LD, the panicle characteristics were measured 35 d after the first panicle emergence (Figure 1J–L; Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Hd2 derived from a cross between Nipponbare and Kasalath (Yano et al, 1997;Yamamoto et al, 1998) and confirmed as OsPRR37 gene (pseudo-response regulator gene) (Koo et al, 2013). Hd2 is allelic with Ghd7.1 (Yan et al, 2013) and through map based cloning approach it was confirmed that Ghd7.1 is the OsPRR37 gene, or Gao et al, (2014) reported Days to heading 7 (DTH7) and Zhang et al, (2016) detected qHD7.2, both of them encodes a pseudo-response regulator protein (OsPRR37).…”
Section: Introductionmentioning
confidence: 92%